Exhibiting Material Localities Through Embodied Sensorial Performance - Paramita, Kristanti Dewi; Riskiyanto, Resza; Harani, Arnis Rochma (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2024)
This study investigates the embodied sensorial performance in material exhibition design as a way to enhance visitors’ experience about local cultures. Exhibitions and installations designed in museum or gallery context often incorporate a sensorial approach to increase engagement and to cater specific needs of society. This study takes particular interest in expanding such discussion, highlighting how a sensorial approach can be used in a more active way to experience localities, particularly in relation with food material.The study explores such sensorial aspects through reflecting towards an exhibition event conducted by the Indonesian Architect Association Central Java titled Rumarasa, an exhibition that explores the sensorial narrative of Indonesian spices. The exhibition consists of three particular stages that activate the overall senses that construct the experience of spices in Indonesia. The first stage consists of the visual stages of the spices, displaying the form and origin of spices in an interactive way. The next stage requires the visitors to touch the spices, inviting the visitors to experience the spice using their tactile, olfactory, and auditory senses. The third stage highlights how the spice can be used as a medium of creative play, transforming the spice as colouring material with different gradients. Through these stages, the sensorial journey constructs the overall local narrative of Indonesian spices, understanding the origin, building the intimacy, and enabling transformation of material. In conclusion, this study contributes to expanding the sensory experience as an approach to design cultural exhibitions, enabling an active and deep experience of locality.